Effect of smartphone use before bedtime on smartphone addiction behaviors among Chinese college students - Li, Linghui; Wang, Lei; Wang, Xinghua (Frontiers in Psychology, 2022)
Smartphone addiction behaviors are becoming more and more common with the rapid popularity and widespread use of smartphones. Such behaviors are significantly influenced by the overuse of smartphones before bedtime. In this study, the overuse of smartphones after 9:00 pm before bedtime was investigated by an online questionnaire. The sample consists of 1,035 college students in China. The artificial neural networks were applied to predict the use time of smartphones before bedtime based on their different usages, and the relationship between smartphone usage and additive behaviors was analyzed. The results show that the neural network model can more accurately predict the usage time of smartphones according to the usage of smartphones before going to bed. At the same time, it is also found that the prediction accuracy of the samples that use the smartphone for less than half an hour and more than 3 h before bed is higher than that of other samples. Moreover, watching short videos and playing games are more likely to lead to mobile phone addiction behavior. These findings would help guide college students to correctly use phones and reduce smartphone addition, which is of great significance for mental health education.